The perception of air pollution and its health risk: a scoping review of measures and methods - Zeinab Bahrami; Satomi Sato; Zhesi Yang; Monali Maiti; Paoin Kanawat; Tomohiro Umemura; Kazunari Onishi; Hiroaki Terasaki; Tomoki Nakayama; Yutaka Matsumi; Kayo Ueda (Global Health Action)
Background Although there is increasing awareness of the health risks of air pollution as a global issue, few studies have focused on the methods for assessing individuals’ perceptions of these risks. This scoping review aimed to identify previous research evaluating individuals’ perceptions of air pollution and its health effects, and to explore the measurement of perceptions, as a key resource for health behaviour. Methods The review followed the methodological framework proposed by Arksey and O’Malley. PubMed and Web of Science were searched. After initial and full-text screening, we further selected studies with standardised scales that had previously been tested for reliability and validity in assessing awareness and perceptions. Results After full-text screening, 95 studies were identified. ‘Perception/awareness of air quality’ was often measured, as well as ‘Perception of health risk.’ Only nine studies (9.5%) used validated scaled questionnaires. There was considerable variation in the scales used to measure the multiple dimensions of risk perception for air pollution. Conclusion Few studies used structured scales to quantify individuals’ perceptions, limiting comparisons among studies. Standardised methods for measuring health risk perception are needed.